2012
DOI: 10.1039/c2jm35110b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and photocatalytic activity of Cu-doped Zn/ZnO photocatalyst with carbon modification

Abstract: Herein, we report the preparation of Cu-doped Zn/ZnO composites with carbon modification via a simple replacement-hydrothermal method using Zn powder and CuSO 4 $5H 2 O as raw materials. The as-synthesized composites were characterized by powder X-ray diffraction (XRD), UV-visible diffuse reflectance spectroscopy (DRS), X-ray photoelectron spectroscopy (XPS) and photoluminescence spectroscopy (PL). The results showed that Cu doping promotes crystal growth of ZnO, inhibits phase transfer of metallic Zn to ZnO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 73 publications
3
17
1
Order By: Relevance
“…This is because at this amount (1.5%) of Cu dopant, very few substitutional Zn sites are available. This corroborates with the findings of Wang et al, where they found grain size is reduced when doping large amounts of Cu into ZnO thin films 69,70 . The values of D and δ are shown in Table 1.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This is because at this amount (1.5%) of Cu dopant, very few substitutional Zn sites are available. This corroborates with the findings of Wang et al, where they found grain size is reduced when doping large amounts of Cu into ZnO thin films 69,70 . The values of D and δ are shown in Table 1.…”
Section: Resultssupporting
confidence: 91%
“…The d-spacing value of (1.5% Cu and 1% Ti) co-doped ZnO thin film decreases slightly, because at this Cu percentage (1.5%), very few interstitial Zn sites are available. 69,70…”
Section: Interplanar Spacing (D)mentioning
confidence: 99%
See 1 more Smart Citation
“…Before the recombination step can take place, the charge carriers must be trapped by either intrinsic defects in the lattice or extrinsic dopants to increase the lifetime of photoinduced electron–hole pairs 21. Since the reduction of Cu 2+ is thermodynamically feasible in the case of Cu 2+ ‐doped Ba 3 V 2 O 8 , it is reasonable to assume that electrons can be trapped by Cu 2+ , which acts as a sink for photogenerated electrons, reducing the rate of recombination with holes 22. As discussed earlier, nitrogen doping endows intrinsic defects such as oxygen vacancies that are shallow traps for the excited electrons, whereas the holes are trapped by the doped nitrogen, leading to the constraint of recombination of photoinduced electron–hole pairs.…”
Section: Resultsmentioning
confidence: 99%
“…Different papers report the use of Cu-doped ZnO as an effective photocatalytic material [31,40]. However, this photocatalyst was studied mainly for the degradation of organic pollutants from water and wastewater [40][41][42][43]. In the recent years, the effect of Cu ions in ZnO nanorod arrays for photoelectrochemical water splitting under visible light was investigated [44].…”
Section: Introductionmentioning
confidence: 99%